Hemostatic Abnormalities in Dementia: A Systematic Review and Meta-Analysis - Loures, Cristina de Mello Gomide; Duarte, Rita Carolina Figueiredo; Silva, Marcos Vinícius Ferreira; Cicarini, Walter Batista; de Souza, Leonardo Cruz; Caramelli, Paulo; Borges, Karina Braga Gomes; Carvalho, Maria das Graças (Seminars in Thrombosis and Hemostasis, 2019)
Alzheimer's disease (AD) is considered the most frequent cause of dementia. It is known that vascular risk factors play an important role in the development and progression of this condition. Alterations in vascular walls represent documented findings in patients with AD and other dementias affecting elderly people. The authors performed a systematic review and meta-analysis, aiming to synthesize observational studies that evaluated how the hemostatic system may contribute to cognitive decline in the elderly, using papers published until April 2018 and as indexed in Medline (PubMed), Scopus, Web of Science, ScienceDirect, Lilacs, Cinahl, PsycINFO, Cochrane Central Register of Controlled Trials, and Cochrane Database of Systematic Reviews. Among 5,278 studies identified, 32 were included in the final synthesis, and these included 485 patients with mild cognitive impairment, 568 with vascular dementia (VD), 1,781 with AD, and 2,855 participants without dementia. AD patients had increased plasma von Willebrand factor (VWF) (standardized mean difference [SMD]: 2.53; 95% confidence interval [CI]: 0.10–4.95), D-dimer (SMD: 0.50; 95% CI: 0.35–0.66), plasminogen activator inhibitor-1 (SMD: 3.34; 95% CI: 1.01–5.67), thrombomodulin (SMD: 1.08; 95% CI: 0.53–1.62), and homocysteine levels (SMD: 0.65; 95% CI: 0.15–1.15). In contrast, the VD group showed increased fibrinogen levels (SMD: 0.77; 95% CI: 0.13–1.41), activated factor VII (SMD: 0.36; 95% CI: 0.05–0.67), factor VIII (SMD: 0.57; 95% CI: 0.22–0.91), VWF (SMD: 2.34; 95% CI: 0.38–4.29), D-dimer (SMD: 1.14; 95% CI: 0.51–1.78), and homocysteine (SMD: 2.17; 95% CI: 1.67–2.68). AD showed an elevation in some markers of endothelial dysfunction, whereas VD presented mostly an involvement of coagulation cascade components.
Keywords: alzheimer's disease; cognitive decline; dementia; hemostasis